The Public Communication of Science and Non-Formal Education Within the Framework of Public Argentine Archaeology: The Case of Archaeology Workshops - Conforti, María Eugenia (2013)
This article presents and analyses a method of public communication in archaeology carried out by a group of researchers within a non-formal educational framework, as a contribution to public archaeology in Argentina. This project included diverse activities, such as archaeology workshops for children and teenagers, which took place in museums in four cities located in three regions: Paraná (North-east), Tres Arroyos and Lobería (Pampas), and Lamarque (Patagonia). A conceptual evaluation is presented based on the application of a non-participational observation methodology, that includes the analysis of posters made by those attending the workshop and surveys conducted by the archaeologists at the culmination of the activity. This study suggests that workshops can be one of the most effective strategies employed by researchers to publicly communicate archaeology, and therefore can be of use to other research teams that have as their objective the democratization of knowledge generated in scientiﬁc-academic spheres.